Review of the Potential Therapeutic Effects and Molecular Mechanisms of Resveratrol on Endometriosis - Jiang T; Chen Y; Gu X; Miao M; Hu D; Zhou H; Chen J; Teichmann AT; Yang Y (Dove Medical Press, 2023)
Tao Jiang,1,* Yuan Chen,1,* Xia Gu,1,2 Mengyue Miao,1 Daifeng Hu,1 Hui Zhou,1 Jing Chen,3 Alexander Tobias Teichmann,1 Youzhe Yang1,2 1Sichuan Provincial Center for Gynaecology and Breast Diseases, The Affiliated Hospital of Southwest Medical University, Luzhou, 646000, People's Republic of China; 2Academician (Expert) Workstation of Sichuan Province, Luzhou, 646000, People's Republic of China; 3Reproductive Medicine Center, The Second People's Hospital of Yibin, Yibin, 644000, People's Republic of China*These authors contributed equally to this workCorrespondence: Alexander Tobias Teichmann; Youzhe Yang, The Affiliated Hospital of Southwest Medical University, No. 25 Taiping Street, Jiangyang District, Luzhou, 646000, People's Republic of China, Email alexandertobiasteichmann@swmu.edu.cn; yangyouzhe@swmu.edu.cnAbstract: Endometriosis is a hormone-dependent inflammatory disease characterized by the existence of endometrial tissues outside the uterine cavity. Pharmacotherapy and surgery are the current dominant management options for endometriosis. The greater incidence of recurrence and reoperation after surgical treatment as well as the adverse effects of medical approaches predispose patients to potential limitations for their long-term usage. Consequently, it is essential to explore novel supplementary and alternative drugs to ameliorate the therapeutic outcomes of endometriotic patients. Resveratrol is a phenolic compound that has attracted increasing interest from many researchers due to its pleiotropic biological activities. Here, we review the possible therapeutic efficacies and molecular mechanisms of resveratrol against endometriosis based on in vitro, animal, and clinical studies. The potential mechanisms of resveratrol include anti-proliferative, pro-apoptotic, anti-angiogenic, anti-oxidative stress, anti-invasive and anti-adhesive effects, thereby suggesting that resveratrol is a promising candidate for endometriosis. Because most studies have investigated the effectiveness of resveratrol on endometriosis via in vitro trials and/or experimental animal models, further high-quality clinical trials should be undertaken to comprehensively estimate the clinical application feasibility of resveratrol on endometriosis.Keywords: endometriosis, resveratrol, therapeutic efficacies, molecular mechanisms, clinical application